Change in Impairment following Operative Treatment of Degenerative Cervical Myelopathy: A Systematic Review and Meta-Analysis. Issue 1 (April 2016) - Shamji, Mohammed; Tetreault, Lindsay; Kurpad, Shekar; Brodke, Darrel; Smith, Justin; Arnold, Paul; Brodt, Erika; Dettori, Joseph; Fehlings, Michael
Introduction: The primary objective of this work was to define the neurological benefit conferred by surgical intervention to patients with degenerative cervical myelopathy (DCM). Secondary objectives included assessing how preoperative disease severity and duration impacted on that benefit and defining the surgical complications encountered by these patients. Material and Methods: A search was undertaken for articles published until May 2015 evaluating the operative treatment of DCM using electronic databases. Prospective studies of adult surgical myelopathic patients were included. Extracted data included study design, patient demographics, diagnosis, surgical approach, preoperative and postoperative neurological status (mJOA, NDI, Nurick, VAS), and complications. Preoperative disease severity and duration of symptoms were recorded. Risk of bias (Newcastle-Ottawa Scale) and quality of evidence (Grades of Recommendation Assessment, Development and Evaluation) were assessed. Primary outcomes included assessment of change in neurological (graded by mJOA, NDI, and Nurick scores) and pain (graded by VAS score) following surgical intervention for myelopathic patients. Secondary outcomes were also assessed for dependency on preoperative duration of symptoms and preoperative disease severity. Safety of surgery was assessed by pooled estimates of perioperative complications encountered. Results: Among 32 included studies, surgical intervention for DCM patients provided clinically-significant improvement in neurological dysfunction and pain. This improvement occurred at short-term assessment (fewer than 12 months) and was durable in longer-term (greater than 36 months), consistent over several different scoring systems. Shorter duration of symptoms may be associated with a higher likelihood of neurological recovery. Conclusion: Surgical intervention for DCM is an appropriate evidence-based therapy with an acceptably low rate of perioperative complication. Further work is important to define optimal surgical approach and timing.